Is Metabolic Rate Increased in Insomnia Disorder? A Systematic Review - Chapman, Julia L.; Comas, Maria; Hoyos, Camilla M.; Bartlett, Delwyn J.; Grunstein, Ronald R.; Gordon, Christopher J. (Frontiers in Endocrinology, 2018)
Background Insomnia disorder is a highly prevalent health condition, affecting approximately 10-15% of the adult population worldwide. A central feature of insomnia is hyperarousal characterised as persistent and increased somatic, cognitive and cortical stimulation. Hyperarousal leads to a state of conditioned arousal that disrupts both sleep and daytime function. Research studies have shown increases in body temperature, heart rate, electroencephalographic activity, catecholamines, and oxygen consumption as a measure of metabolic rate. These findings provide evidence of increased physiological activation in insomnia however results are not consistent. The aim of the systematic review was to determine if metabolic rate in patients with insomnia is increased in keeping with the hyperarousal hypothesis. Methods We searched Pubmed, Web of Science, CINAHL, PsycINFO, EMBASE and Scopus databases for observational and interventional studies that have measured metabolic rate in insomnia. Study characteristics were extracted and summarized and a risk of bias was performed for each of the studies. Results Two reviewers screened 963 abstracts with 35 articles of interest for full-text review. Four articles evaluating 75 participants were included in this systematic review. Two studies showed increased oxygen consumption across 24 hours in insomnia patients compared with good-sleeping controls. One study which measured oxygen consumption at only a single timepoint showed no difference between insomnia patients and good-sleeping controls. A further study evaluating the effect of lorazepam on oxygen consumption in patients with chronic insomnia showed that lorazepam reduced metabolic rate during the night time only. Conclusions These findings show that metabolic rate appears to be increased across 24 hours in line with the hyperarousal model of insomnia. However, these increases in metabolic rate in insomnia were minor compared to good-sleeping controls and the clinical significance is unclear. Larger, methodologically robust studies are required to confirm these findings and the effect of any increase in metabolic rate on sleep-wake disturbances or pathophysiology.